Analisis Minat Guru dalam Mengadopsi LMS Sokrates di SMP dan SMA-K Strada Tangerang - Liniarti, Tri; Susanto, Hendro (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2024)
This study aims to analyze teachers' interest in adopting Socrates LMS using TAM. Data were collected through pretest, interviews, and online surveys on 123 junior high and senior high school teachers at Strada schools and hypothesis testing was processed using SmartPLS 4.0. The results showed that perceived ease had a positive and significant effect on perceived usefulness, while perceived ease and perceived usefulness had a positive effect on teachers' attitudes in using Socrates LMS. Perceived usefulness had a positive and significant effect on teachers' interest, while perceived ease did not have an effect on teachers' interest in using Socrates LMS. Teachers' attitudes toward Socrates LMS had a positive and significant effect on teachers' interest. In addition, perceived ease and perceived usefulness had a positive and significant effect on interest in using mediated by teachers' attitudes toward Socrates LMS. This study provides implications for the Strada Association to be able to set strategies to build user trust so as to foster interest in using Socrates LMS.